Dehydroepiandrosterone impacts working memory by shaping cortico-hippocampal structural covariance during development. (December 2017) - Nguyen, Tuong-Vi; Wu, Mia; Lew, Jimin; Albaugh, Matthew D; Botteron, Kelly N; Hudziak, James J; Fonov, Vladimir S; Collins, D. Louis; Campbell, Benjamin C; Booij, Linda; Herba, Catherine; Monnier, Patricia; et al.
Highlights: Insular-hippocampal structural covariance varies as a function of DHEA levels. Occipito-hippocampal structural covariance varies as a function of DHEA levels. Working memory varied according to the development of cortico-hippocampal networks. DHEA-related cortico-hippocampal networks may play a role in working memory. Abstract: Existing studies suggest that dehydroepiandrosterone (DHEA) may be important for human brain development and cognition. For example, molecular studies have hinted at the critical role of DHEA in enhancing brain plasticity. Studies of human brain development also support the notion that DHEA is involved in preserving cortical plasticity. Further, some, though not all, studies show that DHEA administration may lead to improvements in working memory in adults. Yet these findings remain limited by an incomplete understanding of the specific neuroanatomical mechanisms through which DHEA may impact the CNS during development. Here we examined associations between DHEA, cortico-hippocampal structural covariance, and working memory (216 participants [female=123], age range 6–22 years old, mean age: 13.6 +/−3.6 years, each followed for a maximum of 3 visits over the course of 4 years). In addition to administering performance-based, spatial working memory tests to these children, we also collected ecological, parent ratings of working memory in everyday situations. We found that increasingly higher DHEA levels were associated with a shift toward positive insular-hippocampal and occipito-hippocampal structural covariance. In turn, DHEA-related insular-hippocampal covariance was associated with lower spatial working memory but higher overall working memory as measured by the ecological parent ratings. Taken together with previous research, these results support the hypothesis that DHEA may optimize cortical functions related to general attentional and working memory processes, but impair the development of bottom-up, hippocampal-to-cortical connections, resulting in impaired encoding of spatial cues.